A new predictive equation for estimating wave period of subaerial solid-block landslide-generated waves. Issue 1 (2nd January 2023) - Sabeti, Ramtin; Heidarzadeh, Mohammad
ABSTRACT: In the aftermath of the deadly 2018 Anak Krakatau tsunami (Indonesia) and associated confusions over its modeling and generation mechanism, there has been an urgent need for further studies to improve our understanding of landslide-generated tsunamis. Two important factors in accurate modeling of landslide tsunamis are the wave period and the initial wave amplitude. Here, we apply a physical modeling approach and develop an empirical equation to predict the dominant wave period generated by solid-block subaerial landslide tsunamis. Fifty-one laboratory experiments are conducted at different water depths and using four different concrete blocks for the sliding masses. The results are consequently employed to derive a predictive equation for the wave period of solid-block subaerial landslide tsunamis. An innovation of this study is that we apply data from different scales (laboratory and field scales) to produce our predictive equation. For field data, the data from the 2018 Anak Krakatau event is used. We compared our predictive equation with other previously-published equations. To confirm the validity of our predictive equation, it is applied for the prediction of the wave period of an independent landslide tsunami event whose data was not used for the derivation of the equation.